Hammer-head turn flight control of helicopters by using a thrust selection / desired attitude calculation based on a loading trajectory and a threshold - Daigo FUJIWARA (Nihon Kikai Gakkai ronbunshu, 2021)
The design method for reference trajectory calculation and flight control system development of the autonomous hammer-head turn maneuver and verification results applied to unmanned helicopters are described. The whole maneuver is divided into four processes. Polynomial of the load factor is formulated by using trigonomeric functions and the given attitude trajectories. Coefficients of the polynomial are calculated by solving simultateous equations which include velocity/load-factor terminal conditions at the beginning and the end of each process. It is introduced in the velocity control law that the reference thrust is selected by looking a value of a reference load factor. This reduces effects to the desired attitude delivered from velocity tracking errors to complete vertical pitch-up motion around the turn process. The results of computational simulations and outdoor flight tests by using the experimental apparatus including a small flybar-less electric helicopter show that the desired maneuver which covers low-to-high speed and load over 2-G is safely achieved by using the proposed methods. On the other hand, velocity tracking performance deteriorates for a while after turn because of priority of pitch up. Rotor-speed drop-down often occurs during climb up against the wind because of lack of motor torque of the experimental helicopter.